2003
DOI: 10.1111/j.1572-0241.2003.08769.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of N-Butyl-2-Cyanoacrylate (Histoacryl) Glue Injections Versus Transjugular Intrahepatic Portosystemic Shunt in The Management of Acute Gastric Variceal Bleeding

Abstract: In this comparable group of patients, cyanoacrylate glue injection was more cost effective than TIPS in the management of acute gastric variceal bleeding. A prospective, randomized trial would be required to confirm our analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(81 citation statements)
references
References 23 publications
2
79
0
Order By: Relevance
“…Th e fi ndings of our single-center retrospective study confi rm results reported by Rengstorff et al ( 6 ) and Monsanto et al ( 7 ), where the use of cyanoacrylate injection is very eff ective in controlling gastric variceal bleeding with an acceptable safety profi le. Studies from China, Portugal, and the United States have reported rebleeding rates in the range of 4% to 14.4% (6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…Th e fi ndings of our single-center retrospective study confi rm results reported by Rengstorff et al ( 6 ) and Monsanto et al ( 7 ), where the use of cyanoacrylate injection is very eff ective in controlling gastric variceal bleeding with an acceptable safety profi le. Studies from China, Portugal, and the United States have reported rebleeding rates in the range of 4% to 14.4% (6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…Although the available literature on GV bleeding is not as robust as the one for EV, all studies comparing TIPS vs. cyanoacrylate in bleeding GV demonstrated a significantly higher success rate in the TIPS group, with a greater burden of HE in derived subjects [14,[115][116][117][118][119][120][121][122][123]; In patients with large gastro renal shunts and contraindications to TIPS (e.g. elderly patients or patients with refractory encephalopathy or more compromised liver function) BRTO may be considered for the treatment of GV bleeding [124][125][126][127][128].…”
Section: Tips Is Not Indicated For the Prophylaxis Of First Variceal mentioning
confidence: 99%
“…18 Costeffective analyses comparing NBC injection with TIPS have suggested that NBC is a safe and effective treatment for gastric variceal bleeding that can be provided at a significantly lower cost compared with TIPS placement. 19,20 The usefulness of TIPS is also limited by its availability only in major centers. 17 Balloon occluded retrograde transvenous obliteration has been used successfully for GV obliteration, primarily in Japan, as an elective procedure, but is unsuitable for acute gastric variceal bleeding and requires the presence of a spontaneous gastro-renal shunt.…”
Section: Discussionmentioning
confidence: 99%